Effectiveness of Electroacupuncture in Patients with Chronic Fatigue Syndrome: A Systematic Review and Meta-analysis - Jaewoo Yang; Donghoon Shin; Jihoon Oh; Jinwoong Lim (MEDrang Inc., 2022)
This review evaluated the efficacy of electroacupuncture (EA) for chronic fatigue syndrome. Randomized controlled trials (RCTs) using EA as an intervention for patients with chronic fatigue syndrome were identified in 6 databases (PUBMED, EMBASE, CNKI, J-STAGE, KMBASE, OASIS). Fatigue indicators were used as the primary outcome measures. The quality-of-life index, efficiency rate, and level of pain were used as secondary outcome measures. There were 408 patients from seven RCTs included in this study. Meta-analysis showed that EA was significantly associated with fatigue relief compared with the control group (n = 141 SMD = −1.55, 95% CI: −2.58 - −0.52, p = 0.003, I2 = 92%). In addition, EA had a statistically significant improvement in quality of life compared with the control group (n = 176, SMD = −2.29, 95% CI: −3.68 - −0.90, p = 0.001, I2 = 96%). One study reported ten cases of bleeding, however, no serious adverse events were reported in any of the included studies. This review determined that EA may have a greater clinical effect than the control group for fatigue relief and improved quality of life. However, there were several risks of bias identified. Not all of the RCTs accurately reported the research method, all studies were conducted in 1 country (China), and the number of studies included were small.